Increasing HOTS of High School Students Using Mobile Technology and Scaffolding Approach: Study on Physics Learning - Singgih Hutomo Aji; Suparno (JTP - Jurnal Teknologi Pendidikan, 2020)
Improvement, development, and growth of a country cannot be separated from the quality of its human resources. This is even more so for a country that will face a population demographic bonus like Indonesia, which requires excellent and increasing quality of human resources so that they are always able to compete. Education is one of the factors that plays an important role in advancing the quality of human resources. This study aims to develop an Android-based learning media application on simple harmonic motion physics material and is used to improve the HOTS ability of students by learning using the scaffolding approach. This study is an R&D with a 4D model consisting of the Defining, Designing, Developing, and Disseminating stages. The operational test at the Developing stage was carried out using an experiment with the Pretest-Posttest Control Group design. The product in this study is an Android-based physics learning media application on simple harmonic motion material that has been tested for its feasibility for use in physics learning. Then, the product was tested in the field by being implemented in learning. The experimental results in the experimental class using android media and the scaffolding approach and the control class using conventional learning showed a significant difference in HOTS abilities. The implementation of Android-based physics mobile learning media and the scaffolding learning approach has a positive effect on the HOTS ability of students.